Training approaches for the dissemination of clinical guidelines for NSSI: a quasi-experimental trial - König, Elisa; Hoffmann, Ulrike; Fegert, Jörg M.; Keller, Ferdinand; Sicorello, Maurizio; Spohrs, Jennifer; Kraus, Laura; Nickel, Sandra; Schmahl, Christian; Abler, Birgit; In-Albon, Tina; Koenig, Julian; et al. (Child and adolescent psychiatry and mental health, 2024)
Non-suicidal self-injury (NSSI) is of high clinical relevance due to its high prevalence and negative long-term implications. In 2016, the German consensus-based clinical guidelines for diagnostic, assessment and treatment of NSSI in childhood and adolescence were published. However, research indicates that clinical guidelines are often poorly implemented in clinical practice. One crucial part of this process is the training of healthcare professionals to transfer knowledge and capacities to bring guideline recommendations into clinical practice. The effect of three different dissemination strategies (printed educational material, e-learning, and blended-learning) on the NSSI guidelines´ recommendations was examined among 671 physicians and psychotherapists via an online-survey. The quasi-experimental study included three measurement points (before the training, after the training, 3-month follow-up) and mixed effects models were used to test for changes in knowledge, competences and attitudes toward NSSI and treatment. Moreover, the transfer of gained competences to practical work and user satisfaction were reviewed. With all three training formats, the intended changes of the outcome variables could be observed. Hereby, the printed educational material condition showed the lowest improvement in the scores for the ‘negative attitudes toward NSSI and those who self-injure’. The training effect remained stable throughout the follow-up measurement. The highest application rate of acquired intervention techniques in clinical practice was reported for the blended-learning condition. For all three training strategies, user satisfaction was high and evaluation of training quality was positive, with printed educational material receiving the lowest and blended-learning the highest evaluations. In summary, all three training formats were perceived to be of high quality and seem to be suited to cover the needs of a heterogeneous group of physicians and psychotherapists. The choice of training method could be driven by considering which training goals are desired to be achieved and by the benefit-cost ratio allowing for tailored training approaches.
Gesehen am 25.02.2025
Mitglieder des STAR-Consortiums sind: Paul L. Plener (Department for Child and Adolescent Psychiatry/Psychotherapy, Ulm University Hospital, Ulm, Germany, Department of Child and Adolescent Psychiatry, Medical University of Vienna, Vienna, Austria), Jennifer Spohrs (Department for Child and Adolescent Psychiatry/Psychotherapy, Ulm University Hospital, Ulm, Germany), Birgit Abler (Department of Psychiatry and Psychotherapy III, Ulm University, Ulm, Germany), Sandra Nickel (Department for Child and Adolescent Psychiatry/Psychotherapy, Ulm University Hospital, Ulm, Germany), Elisa Sittenberger (Department of Psychiatry and Psychotherapy III, Ulm University, Ulm, Germany), Lisa Schischke (Department of Psychosomatic Medicine and Psychotherapy, Ulm University Medical Centre, Ulm, Germany), Alina Geprägs (Department for Child and Adolescent Psychiatry/Psychotherapy, Ulm University Hospital, Ulm, Germany), Isabell Liebhart (Department for Child and Adolescent Psychiatry/Psychotherapy, Ulm University Hospital, Ulm, Germany), Andreas Witt (University Hospital of Child and Adolescent Psychiatry and Psychotherapy, University of Bern, Bern, Switzerland), Cedric Sachser (Department for Child and Adolescent Psychiatry/Psychotherapy, Ulm University Hospital, Ulm, Germany), Rebecca Brown (Department for Child and Adolescent Psychiatry/Psychotherapy, Ulm University Hospital, Ulm, Germany), Vera Münch (Department of Paediatrics and Adolescent Medicine, Ulm University Medical Centre, Ulm, Germany), Elisa König (Department for Child and Adolescent Psychiatry/Psychotherapy, Ulm University Hospital, Ulm, Germany), Jörg M. Fegert (Department for Child and Adolescent Psychiatry/Psychotherapy, Ulm University Hospital, Ulm, Germany), Ulrike Hoffmann (Department for Child and Adolescent Psychiatry/Psychotherapy, Ulm University Hospital, Ulm, Germany), Christian Schmahl (Department of Psychosomatic Medicine and Psychotherapy, Central Institute of Mental Health Mannheim, Medical Faculty Mannheim, Heidelberg University, Mannheim, Germany), Inga Niedtfeld (Department of Psychosomatic Medicine and Psychotherapy, Central Institute of Mental Health Mannheim, Medical Faculty Mannheim, Heidelberg University, Mannheim, Germany), Maurizio Sicorello (Department of Psychosomatic Medicine and Psychotherapy, Central Institute of Mental Health Mannheim, Medical Faculty Mannheim, Heidelberg University, Mannheim, Germany), Jenny Zähringer (Department of Psychosomatic Medicine and Psychotherapy, Central Institute of Mental Health Mannheim, Medical Faculty Mannheim, Heidelberg University, Mannheim, Germany), Tina In-Albon (Clinical Child and Adolescent Psychology and Psychotherapy, University of Kaiserslautern-Landau, Landau, Germany), Laura Kraus (Clinical Child and Adolescent Psychology and Psychotherapy, University of Kaiserslautern-Landau, Landau, Germany), Hasan-Hüseyin Isik (Clinical Child and Adolescent Psychology and Psychotherapy, University of Kaiserslautern-Landau, Landau, Germany),Michael Koelch (Department of Child and Adolescent Psychiatry, Neurology, Psychosomatics, and Psychotherapy, University Medical Centre Rostock, Rostock, Germany), Olaf Reis (Department of Child and Adolescent Psychiatry, Neurology, Psychosomatics, and Psychotherapy, University Medical Centre Rostock, Rostock, Germany), Anna Michelsen (Department of Child and Adolescent Psychiatry, Neurology, Psychosomatics, and Psychotherapy, University Medical Centre Rostock, Rostock, Germany), Andreas G. Chiocchetti (Department of Child and Adolescent Psychiatry, Psychosomatics and Psychotherapy, University Hospital Frankfurt, Goethe-Universität, Frankfurt am Main, Germany), Silvia Lindlar (Department of Child and Adolescent Psychiatry, Psychosomatics and Psychotherapy, University Hospital Frankfurt, Goethe-Universität, Frankfurt am Main, Germany), Regina Waltes (Department of Child and Adolescent Psychiatry, Psychosomatics and Psychotherapy, University Hospital Frankfurt, Goethe-Universität, Frankfurt am Main, Germany), Michael Kaess (Department of Child and Adolescent Psychiatry, Centre for Psychosocial Medicine, Heidelberg University, Heidelberg, Germany, University Hospital of Child and Adolescent Psychiatry and Psychotherapy, University of Bern, Bern, Switzerland), Julian Koenig (Department of Child and Adolescent Psychiatry, Psychosomatics and Psychotherapy, Faculty of Medicine and University Hospital Cologne, University of Cologne, Cologne, Germany), Markus Mössner (Department of Child and Adolescent Psychiatry, Centre for Psychosocial Medicine, Heidelberg University, Heidelberg, Germany), Patrice van der Venne (Department of Child and Adolescent Psychiatry, Centre for Psychosocial Medicine, Heidelberg University, Heidelberg, Germany), Saskia Höper (Department of Child and Adolescent Psychiatry, Centre for Psychosocial Medicine, Heidelberg University, Heidelberg, Germany), Elisa Flach (Department of Child and Adolescent Psychiatry, Centre for Psychosocial Medicine, Heidelberg University, Heidelberg, Germany), Alexandra Edinger (Department of Child and Adolescent Psychiatry, Centre for Psychosocial Medicine, Heidelberg University, Heidelberg, Germany), Stephanie Bauer (Department of Child and Adolescent Psychiatry, Centre for Psychosocial Medicine, Heidelberg University, Heidelberg, Germany), Margarete Mattern (Department of Child and Adolescent Psychiatry, Centre for Psychosocial Medicine, Heidelberg University, Heidelberg, Germany), Sabine Herpertz (Department of Child and Adolescent Psychiatry, Centre for Psychosocial Medicine, Heidelberg University, Heidelberg, Germany), Ulrich Ebner (Mental mHealth Lab, Chair of Applied Psychology, Institute of Sports and Sports Science, Karlsruhe Institute of Technology (KIT), Germany), Philip S. Santangelo (Mental mHealth Lab, Chair of Applied Psychology, Institute of Sports and Sports Science, Karlsruhe Institute of Technology (KIT), Germany)